Itineraries and Domains of Fikh in the Upper Middle Ages: The communication between Maliki jurists in the Orient and the Occident (Journal of the College of Basic Education, 2023)
The Islamic Maghreb is distinguished by the legal and social dominance of the Maliki school of thought..The charisma of its jurists and the “power of the Sultan” allied to spread throughout Morocco and Andalusia and dominate its institutions. The Malikis established a strict doctrinal system that got rid of all its competitors from the Awza’is Hanafis Dhahiries Idrisides and Ismailis!The Malikis did not dispense with the knowledge of the oriental Malikis, so the distribution of knowledge were active towards the Orient since Malik throughout the Middle Ages, for pilgrimage and educational attainment by the scientists of Mecca Medina and Iraq. And if there are many justifications for the dominance of the Maliki school of thought, and the Moroccans’ adherence to and aversion to the rest of the schools. While Ibn Hazm Al-Dhaheri acknowledged: "Two doctrines spread at the beginning of their command of leadership and power, the doctrine of Abu Hanifa and the doctrine of Malik bin Anas." Ibn Khaldun explained it with several subjective and objective factors. Does this explain the persistence of the Maliki kingdom of Morocco and its continuity to this day?